2022
DOI: 10.1002/acs.3457
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive neural tracking control for non‐affine switched systems with multiple time delays and actuator faults

Abstract: Summary In this article, an adaptive output feedback neural tracking control algorithm is studied for non‐affine switched systems with multiple time delays and actuator faults. First, an adaptive neural state observer, which only needs to update a parameter online, is presented to estimate the unmeasurable state, and Lipschitz condition is used to deal with delay fault so as to avoid complex delay assumption. Then, by using online estimation information and backstepping technique, a switched fault‐tolerant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…On the other hand, most practical control systems are nonlinear in essence 19‐23 . Thus, the nonlinear characteristics can not be overlooked in fault estimation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, most practical control systems are nonlinear in essence 19‐23 . Thus, the nonlinear characteristics can not be overlooked in fault estimation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most practical control systems are nonlinear in essence. [19][20][21][22][23] Thus, the nonlinear characteristics can not be overlooked in fault estimation. At present, more and more attention is paid to the research of nonlinear systems for fault estimation and considerable research results have been reported on this topic, such as References 24-30.…”
Section: Introductionmentioning
confidence: 99%
“…In References 34 and 35, two different finite‐time output feedback control methods were designed with a state observer. Compared with the infinite‐time control strategy, 36 the finite‐time control method can make the closed‐loop system converge faster. From the point of convergence time, the control algorithm with finite‐time is a time optimization algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in Reference 24 propose the robust fault estimation and fault‐tolerant control (FTC) method of Takagi‐Sugeno fuzzy systems, where the compensation techniques are utilized to eliminate the effects of actuator fault and sensor fault on the system performance. Some adaptive control approaches are developed for nonlinear systems with actuator faults, for example, References 25,26. Nevertheless, there are fewer results on NN consensus control issues for nonlinear MASs with actuator faults based on event‐triggered mechanisms, which is one reason motivating our research.…”
Section: Introductionmentioning
confidence: 99%